Positivisme Hukum dalam Mengatasi Konflik Hukum Perkawinan Beda Agama - Kaesnube, Yohanes; Riyanto, Armada (Borneo Review, 2023)
Abstract The focus of this study is that interfaith marriages often cause legal conflicts due to religious differences between husband and wife. This legal conflict can be related to various matters such as child custody, distribution of assets, and determination of the child's religion. This becomes complex because each religion has its own rules regarding marriage and family. The purpose of this scientific work is to find out how the legal view of legal positivism in interfaith marriages. Legal positivism is a legal view that emphasizes the importance of written legal rules as the only source of applicable law. In the context of interfaith marriages, legal positivism can play an important role in overcoming legal conflicts that arise. The method used in this scientific paper is a comparative study and literature. There are three findings from this study: First, legal positivism can help parties involved in interfaith marriages to understand the applicable legal rules. Second, legal positivism can help resolve legal conflicts through appropriate legal channels. Third, legal positivism can help ensure legal protection for parties involved in interfaith marriages.